Bilateral arachnoid cyst-associated subdural fluid collections in an infant following TBI. (July 2021) - Canty, Katherine W.; Shiroishi, Mark S.; Zada, Gabriel; Sharma, Supriya; Jimenez, Melissa A.
Abstract: Introduction: arachnoid cyst-associated subdural fluid collections have been documented in children and adults following traumatic brain injury (TBI). However, this phenomenon has not been previously demonstrated in infants less than 12 months of age. We present a case of an infant with bilateral arachnoid cyst-associated subdural fluid collections identified after TBI. Case presentation: a 9-month-old female infant with profound macrocephaly presented to medical care with altered mental status following a witnessed fall down steps while unsecured in a stroller. Neuroimaging revealed bilateral subdural fluid collections, in addition to a hyperdense subdural hematoma, that raised concern for abusive head trauma (AHT) among the pediatric inpatient team and the hospital's Suspected Child Abuse and Neglect (SCAN) Team was consulted. After excluding occult abusive injuries as well as testing for underlying medical conditions, the infant's bilateral subdural fluid collections were attributed to rupture of a pre-existing left middle cranial fossa arachnoid cyst with evidence of prior macrocephaly. Conclusion: In infants and toddlers, the identification of subdural fluid collections on neuroimaging warrants inclusion of AHT in the differential diagnosis. However, in infants with a history of congenital macrocephaly, and an otherwise negative AHT workup, an accidental mechanism for the formation of subdural collections should be considered, especially when co-occurring with an arachnoid cyst. Highlights: Arachnoid-cyst associated subdural collections following TBI are a recognized phenomenon. Until now, this phenomenon had not been reported in an infant under 12 months of age. Familiarity with this association has important forensic implications.